FOREWORD: ANNIVERSARY OF PROFESSOR ROMULUS TETEAN VINTELER - POP, Viorel (Studia Universitatis Babeș-Bolyai Physica, 2022)
I appreciate the opportunity offered by this anniversary issue of the scientific journal Studia Physica to note some important aspects related to the didactic and research activity of professor doctor Romulus Tetean. Profesor Romulus Tetean was born in Sântejude, Cluj County, Romania, on November 11, 1957. He graduated the Faculty of Physics at Babeș-Bolyai University in 1981. Thanks to the exceptional results obtained during his undergraduate studies, Romulus Tetean was among the most meritorious students who attended the Solid State Physics master's degree at Babeș-Bolyai University, graduating in 1982. He pursued his PhD studies between 1993 and 1997 at the same university, under the supervision of professor Emil Burzo. This period allowed him to advance his scientific competences in the field of materials science, more precisely in that of the magnetism of intermetallic compounds of 3d transition metals with rare earths. The scientific research of prof. Tetean was mainly directed to the study of the structural, electronic, magnetic and transport properties of different classes of materials, such as rare earth - 3d transition metal intermetallic compounds, permanent magnets, nanostructured materials, perovskites and superconducting materials with possible technical applications such as permanent magnets, sensors, biomedicine and magnetic refrigeration. He was involved in the preparation of new classes of materials and characterization by X-ray diffraction, X-ray photoelectron spectroscopy (XPS), magnetic susceptibility, magnetization, specific heat, electronic properties, Mossbauer effect, and muon spin rotation and relaxation (μSR).